Diffraction imaging for edge detection - Alonaizi, F.; Pevzner, Roman (2015)
In this work a robust imaging algorithm based on detecting edge diffraction has been developed. The algorithm is based on measuring the coherency of the data using the semblance function computed along the traveltime curve of the diffracted wave. Based on the fact that waveforms on two sides of edge diffraction have opposite polarity, the proposed method exploit the phase-reversal phenomenon of edge diffractions in the computation process and use it as a criterion to separate edge diffractions from specular reflections. Utilizing the phase-reversal property of edge diffraction allows the detection of small features in the subsurface, and image hidden diffracted waves that could be masked by strong reflections. Two examples are provided to illustrate the validity of the method, the first example is a physical model of an edge diffractor, and the second example is real GPR data acquired over a lake.